Impact of complex-valued energy function singularities on the behaviour of rayleighschro dinger perturbation series; 70th International Symposium on Molecular Spectroscopy: ISMS, June 22-26, 2015, Champaign, Urbana, Illinois - Duchko A. N. Andrey Nikolaevich (2015, 2015)
Title screen